Delayed Hardening and Reactivation of Binder Calcite, Common Problems in Radiocarbon Dating of Lime Mortars. Issue 3 (14th June 2020) - Lindroos, Alf; Ringbom, Åsa; Heinemeier, Jan; Hajdas, Irka; Olsen, Jesper
ABSTRACT: When sampling mortars for radiocarbon ( 14 C) dating it is crucial to ensure that the sample has hardened rapidly relative the resolution of the dating method. Soft and porous lime mortars usually fulfill this criterion if the samples are taken from an uncovered surface from less than a few centimeters deep. However, hard, concrete-like mortars may be impermeable for carbon dioxide and even the outermost centimeters may still contain uncarbonated calcium hydroxide. These mortars may harden very slowly and contain carbonate that formed centuries or even millennia after the original building phase, and they can still be alkaline and capture modern 14 C, causing younger 14 C ages than the actual construction age. Another problem is reactivation of the binder carbonate if it has been partly decarbonated during a fire later on in its history. It will be shown that these young carbonates dissolve rapidly in phosphoric acid and in many cases a reasonable 14 C age can be read from 14 C profiles in sequential dissolution if the measurements from initially formed carbon dioxide are disregarded. However, if a mortar was made waterproof deliberately by adding crushed or ground tile, as in Roman cocciopesto mortars, it may be very difficult to get a conclusive dating.